1974
DOI: 10.1161/01.str.5.1.13
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sympathetic Denervation on Cerebral CO 2 Sensitivity

Abstract: Abstract:The Effect of Sympathetic Denervation on Cerebral C Sensitivitv

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1974
1974
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Perhaps norepinephrine failed because it is normally rapidly taken up by sympathetic nerve endings in the area 19 as well as being washed away by the normal flow of CSF. Indeed, the latter may be responsible for the spontaneous reversal of the spasm produced by the various substances tested.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps norepinephrine failed because it is normally rapidly taken up by sympathetic nerve endings in the area 19 as well as being washed away by the normal flow of CSF. Indeed, the latter may be responsible for the spontaneous reversal of the spasm produced by the various substances tested.…”
Section: Discussionmentioning
confidence: 99%
“…Both morphological and physiologi- 1 7 4 KUSCHINSKY, WAHL cal data (5) indicate the existence of sympathetic perivascular nerves at pial arteries, but under what conditions are these nerves activated? From studies using stimulation, denervation, and alphareceptor blockers, it has been suggested that the tone of cerebral arteries may be influenced by sympathetic constrictor nerves under conditions such as changes in arterial Pco 2 (26)(27)(28) or blood pressure (26) or during subarachnoidal hemorrhage or experimental spasm (12,29,30).…”
Section: Discussionmentioning
confidence: 99%
“…9 All of these studies point to a sympathetic vasoconstrictor innervation to the cerebral vessels but this has recently been disputed. Stone, Raichle and Hernandez (1974) 16 using a flowmeter have shown that sympathectomy causes a reduced cerebrovascular dilatation with hypercapnia rather than the enhanced response previously shown. These workers have proposed that the sympathetics are cerebral vasodilators and assist in the reaction to hypercapnia.…”
Section: Discussionmentioning
confidence: 93%